OPERATION BASED COST ASSESSMENT OF MACHINED PARTS IN THE EARLY DESIGN STAGES - Perera, G.I.P. (Journal of Advanced Manufacturing Technology (JAMT), 2014)
Cost is the driving factor of current manufacturing industry. The market is willing to accept products that come at a lower cost. In order to cater such a market, manufacturer has to look to make the product at a lower cost while recovering the expenses. Therefore, the design stage is critical when it comes to achieve this optimum cost. One of the most difficult tasks undertaken by the designer is to evaluate the cost of a design. The designer must develop a design in order to fulfill the required performance characteristics as well as provide the appropriate quality at minimal cost. Substantial research effort has been expanded in exploring design implications, new techniques, and methods for producing accurate and consistent cost estimates not only to generate optimum design solutions but also to achieve the maximum customer satisfaction in terms of low cost, high quality and in time product delivery. This paper focuses on a system developed to estimate the machining cost of a component by analyzing it in the early design phases. The developed system allows the user to consider the part machining operations as well as the manufacturing resources on hand during the analysis stages. A hybrid method, which uses qualitative and quantitative cost estimation techniques, is used in developing the system. The proposed system will be demonstrated and finally, further improvements on the system and its limitation are also discussed.